A study of knowledge and practice of breast feeding in urban slum area under urban health centre in Solapur city, Western Maharashtra - Rajput, Rupali R.; Haralkar, Santosh J.; Mangulikar, Suresh K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Country wide data from National Family Health Survey-III (2005-2006) documented that only 24.5% mothers initiated breastfeeding within desired one hour after the birth and almost 45 percent did not start breastfeeding within one day of birth. As many as 57% women practiced prelacteal feeding, proportion of exclusively breastfed infants at 6 months of age was 46.4%. Methods: The proposed study included cross sectional study of socio-demographic features and breast feeding profile of mothers attending Urban Health Training Centre. 400 mothers of infants aged 6-12 months were interviewed using pretested semi-structured questionnaire. Details about the socio-demographic characteristics and breast feeding practices and knowledge about breast feeding were obtained. Then results were analyzed at the end of data collection. Results: In the present study, out of 400 mothers, 41.25% mothers practice exclusive breast feeding. The knowledge of mothers about the breast feeding, among this knowledge regarding time of initiation of breast feeding after normal delivery and caesarean section was maximum i.e. 93.25%, followed by 57.25% mothers having knowledge regarding duration of exclusive breast feeding. The mothers having minimum knowledge was regarding continuation of breast feeding i.e. 40.25%. Conclusions: This study throws light on the mothers knowledge about breast feeding and what they actually practice. Breastfeeding practices like exclusive breast feeding, prelacteal feeding was less than the national average.